The Success of Transgenders In The Election Process For Public Officials: A Public Policy Reform In Indonesia - Ratnawati Ratnawati (Eduvest - Journal of Universal Studies, 2022)
This study aimed to examine transgender people's success in Indonesia's election for public officials. This victory is the first that happened in the country’s public officials election. As transgenders face discriminative acts which impede their public opportunities, it is interesting to investigate the factors contributing to this election victory. This is a public policy reform in Indonesia. This present study incorporated a focus group discussion (FGD) approach and in-depth interviews. Thirty-two key informants were selected, followed by document reviews. The results showed that the transgender success in elections for public officials is due to utilizing the shift in the heteronormative habitus in society, the possessed capital, and the social domain by building relationships and communication between organizations and institutions. This study contributes to empirical evidence that transgender people could win the election for public officials in a society that firmly holds the values of first and second or male and female gender identity. Practically, it provides input to policymakers to make requirements as public officials limited to men and women and also include transgender as a third gender identity.